Leadership communication styles across corporate governance structures in the Vietnamese banking sector: a comparative analysis - Ngo Thaiduong (Cogent Business & Management)
This study compares leadership communication styles across different corporate governance structures within the Vietnamese banking sector. Content analysis of 120 shareholder letters reveals distinct patterns in how state-owned banks, private banks, family-influenced banks, and banks with foreign strategic alliances emphasize internal collaboration, external pressures, risk management, expansion, innovation, leadership, and social responsibility. State-owned banks prioritize external regulations and individual accountability, reflecting their complex stakeholder environment. In contrast, private banks focus on expansion and visionary leadership, aligning with competitive market pressures. Family-influenced banks demonstrate a reliance on informal networks and growth ambitions, while banks with foreign alliances surprisingly exhibit less emphasis on visionary and social responsibility messaging, potentially reflecting a focus on performance metrics or differing communication norms. This comparative analysis highlights the nuanced ways corporate governance structures shape leadership communication styles, offering valuable insights for practitioners seeking to optimize their communication strategies and for researchers exploring the interplay between corporate structures and leadership behavior in the banking industry.